The Impact of Substitution of Diphenyl Dialumene on the Molecular Structure and Energetic Properties - Salma Babikir; Sahar Abdalla; Wefag Mohamed; Yunusa Umar (Universitas Gadjah Mada, 2024)
The molecular structure, energetic properties, electronic, and vibrational spectroscopy of meta-substituted phenyl dialumene, DPD (Ar–Al=Al–Ar; Ar of the formula C6H5X2, where X = H, CH3, NH2, OH, F, Cl, Br, NO2, and COOH) are investigated by DFT. The singlet states of unsubstituted and substituted DPD adopt trans-planar geometry, while the triplet states adopt non-planar trans-bent geometry. The Al=Al bond length of unsubstituted DPD-H in a singlet state is calculated to be 2.734 Å, and there is no systematic and significant change upon substitution (2.734–2.744 Å). The substitution affects the absolute energy, ionization potential, electron affinity, and reorganization energy. The wavelength of maximum absorbance of DPD-H is determined to be 443 nm, and the substitute analogues DPD-X (X = OH, F, Cl, Br, NO2, CHO, COOH) show a hypsochromic shift, while DPD-CH3 and DPD-NH2 exhibit a bathochromic effect. The HOMO to LUMO+1 transition is the major transition for the meta-substituted DPD, except for X=NO2, where the transition is to LUMO+2. Considering the reorganization energy values, meta-substituted DPD can be useful as hole transporters. In addition, the theoretical data will aid in predicting the behavior of this class of compounds, facilitating the design and synthesis of similar compounds with desired properties.